anonymous
  • anonymous
Solve the equation: (3x - 2)(7x + 1) = 0.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Callisto
  • Callisto
(3x - 2)(7x + 1) = 0 Put (3x - 2) =0 or (7x + 1) = 0 x = 2/3 x=-1/7 actually do you understand how to deal with such kind of questions?
anonymous
  • anonymous
I don;t :(
Callisto
  • Callisto
Give you an easy one to try x (5) = 0, what is x?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
0
Callisto
  • Callisto
How can you get the answer?
anonymous
  • anonymous
Multiplying something by zero always results in a zero.
Callisto
  • Callisto
Yup.. that's the same when you consider the xy=0 What would you think if xy=0? what is the possible value for x or y?
Callisto
  • Callisto
Hint: remember what you've said just now 'Multiplying something by zero always results in a zero.'
anonymous
  • anonymous
I'm not exactly sure how to work the double letters unfortunately. I know if you multiple one by zero it gets zero? I think.
Callisto
  • Callisto
Yup.. you're quite close to the point.. For the product of 2 unknowns, the either one should be =0 to give 0 as the result (of course both of them can be 0), Do you understand so far?
anonymous
  • anonymous
Yeah, I understand so far. Until numbers get added into the situation which makes it twice as difficult.
Callisto
  • Callisto
When you see something like (3x - 2)(7x + 1) = 0. Just consider (3x - 2) =y and (7x + 1)=z So yz=0 Understand so far?
anonymous
  • anonymous
Sort of.
Callisto
  • Callisto
So, either y = 0 or z=0 can make the product =0, understand?
anonymous
  • anonymous
Now it makes more sense.
Callisto
  • Callisto
So remember you let y=(3x - 2) and z=(7x + 1) Put it back to y = 0 or z=0 respectively, and solve for it separately, understand?
anonymous
  • anonymous
That part kind of confuses me the final solve.
Callisto
  • Callisto
Hmmm... which part you don't understand?
anonymous
  • anonymous
So remember you let y=(3x - 2) and z=(7x + 1) Put it back to y = 0 or z=0 respectively, and solve for it separately, understand?
Callisto
  • Callisto
So remember you let y=(3x - 2) and z=(7x + 1) <- understand?
anonymous
  • anonymous
Yes I understand that part.
Callisto
  • Callisto
either y = 0 or z=0 can make the product =0, understand <- understand?
anonymous
  • anonymous
That's where I get confused.
Callisto
  • Callisto
yz=0 either y = 0 or z=0 can make the product =0, understand?
anonymous
  • anonymous
Yeah
Callisto
  • Callisto
so y= 3x-2 =0 or z=7x+1=0, understand?
anonymous
  • anonymous
|dw:1332750990017:dw|
Callisto
  • Callisto
So 3x-2 =0 or 7x+1=0 and solve the 2 equations, understand?
anonymous
  • anonymous
I don't know how to solve them both together.
Callisto
  • Callisto
3x-2 =0 x = 2/3 or 7x+1 =0 x=-1/7 Just solve it separately

Looking for something else?

Not the answer you are looking for? Search for more explanations.